2015
DOI: 10.3109/02699052.2015.1042407
|View full text |Cite
|
Sign up to set email alerts
|

The value of normalization: Group therapy for individuals with brain injury

Abstract: Findings are encouraging and help to validate the effectiveness of group therapy as an intervention tool.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 30 publications
0
7
0
Order By: Relevance
“…Studies examining this construct have noted that when individuals do not understand their experiences (e.g., frequency of cognitive difficulties during menopause, normal age-related changes), they tend to believe their symptoms are unique and that they are less capable or competent than peers which can understandably translate into increased worry ( 92 ). Group interventions facilitate a normalisation process wherein individuals learn that others share their experiences and challenges, and improve adjustment difficulties ( 93 ). Indeed, qualitative information provided by study participants at the post-group assessment indicated a reduction in concerns about dementia following group completion for some, suggesting that their cognitive symptoms were normalised and contextualised.…”
Section: Discussionmentioning
confidence: 99%
“…Studies examining this construct have noted that when individuals do not understand their experiences (e.g., frequency of cognitive difficulties during menopause, normal age-related changes), they tend to believe their symptoms are unique and that they are less capable or competent than peers which can understandably translate into increased worry ( 92 ). Group interventions facilitate a normalisation process wherein individuals learn that others share their experiences and challenges, and improve adjustment difficulties ( 93 ). Indeed, qualitative information provided by study participants at the post-group assessment indicated a reduction in concerns about dementia following group completion for some, suggesting that their cognitive symptoms were normalised and contextualised.…”
Section: Discussionmentioning
confidence: 99%
“…The requirement for therapeutic assistance for both the processing of loss and mourning for pre‐injury self, and in the construction of a new sense of self is evidenced. Previous studies outline that emotional adjustment is the foundation of rehabilitation (von Mensenkampff et al, 2015). This study adds to literature by highlighting that psychotherapy may also be a necessary process in addressing loneliness and social re‐integration for some individuals living with brain injury.…”
Section: Discussionmentioning
confidence: 99%
“…Social isolation and adjustment are significant issues following TBI [3,38,40,41], and the finding that groups contribute to the development of relationships outside of the group provides support for the use of groups even in the early stages of inpatient rehabilitation.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Groups are commonly used in health care [1]. The value of opportunities for peer support and learning, and adjustment following injury or illness are consistently identified in the rehabilitation literature [2][3][4]. Rehabilitation groups can be used for education, to practice skills and strategies, to maximize therapy intensity, and to provide opportunities for peer support [1,2].…”
Section: Introductionmentioning
confidence: 99%